Bolt-joint structural health monitoring by the method of electromechanical impedance. Issue 3 (29th April 2014) - Pavelko, Igor; Pavelko, Vitalijs; Kuznetsov, Sergey; Ozolinsh, Ilmars
Abstract : Purpose: – The purpose of this paper is to present the problems of the electromechanical impedance (EMI), especially its applications for structural health monitoring of aircraft bolt-joints and innovative approach of EMI prediction at loosening of bolt-joints. Design/methodology/approach: – This experimental study includes the results of a full-scale test of the Mi-8 helicopter tail beam, particularly, its bolt-joints of a beam with other parts of the structure. One of the connecting frames of the tail beam was equipped with piezoelectric transducers (PZT) glued on the surface of the frame near the bolts. The bolts' loosening was investigated by using the EMI technology. Findings: – It was demonstrated that loosening of the bolt-joint produces a significant and statistically stable change of the EMI metric. Presumably, both the small shift of resonance frequencies and the EMI magnitude and resistance change are caused mainly by damping variation at the bolt-joint loosening. In this analytical study, the 2D model of a constrained PZT is proposed. In contrast with the existing model, the modal decomposition analysis is used as a universal mean to express the dynamic properties and dynamic responses of both the transducer and the host structure. This approach, together with the finite element modal analysis, allows simulation of any complex system "PZT-host structure". The model can be easily transformed also to the 3D one. The bolt-joint of the Mi-8 helicopter with the EMI measurement system was simulated by using the developed 2D model. The simulation results satisfactorily correspond to the test. Practical implications: – The results of this research can be used for implementation in the structural health monitoring of bolt-joints and other aerospace structural components. Originality/value: – The new experimental results on aircraft real bolt-joints were obtained. Especially significant is the original 2D model of the electromechanical impedance, based on the modal decomposition method, which can significantly improve the accuracy and the realistic description of the dynamic interaction between PZT and structure, as well as the dynamic response to the appearance of structural damage.